2003
DOI: 10.2355/isijinternational.43.1136
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Model for the Uniform Conversion of Self Reducing Iron Oxide and Carbon Briquettes

Abstract: A kinetic model has been developed to describe the uniform conversion of a self reducing mixture of iron oxide and carbon. The model takes into account the reaction kinetics of both the iron oxide reduction and carbon oxidation. The model is validated with experimental data. Rate constants are compared with those in the literature.The combination of existing reaction analysis techniques coupled with the model developed has shown that for the experimental conditions used here, the Boudouard reaction controls th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…They concluded that the direct contact of reduced iron with carbon was crucial for low temperature melting and flux addition is the most effective method to remove gangue layer which blocks melting of reduced iron. Our previous work has developed a kinetic model which is suitable for self-reducing iron oxide pellet, 6) and more recently the authors have examined the role of the Boudouard reaction in iron oxide and carbon briquettes.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the direct contact of reduced iron with carbon was crucial for low temperature melting and flux addition is the most effective method to remove gangue layer which blocks melting of reduced iron. Our previous work has developed a kinetic model which is suitable for self-reducing iron oxide pellet, 6) and more recently the authors have examined the role of the Boudouard reaction in iron oxide and carbon briquettes.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] . It is well established idea that the Boudouard reaction is significantly slower than the reduction of iron oxide below 1 473 K (1 200°C), 23,24) so the overall reaction rate is controlled by Eq. (3).…”
Section: Reaction Mechanism Of Carbon Composite Pelletsmentioning
confidence: 99%
“…23,24) When solid carbon reacts with solid iron oxide in carbon composite pellet, the overall reaction is largely influenced by the reaction in Eq. (6).…”
Section: Influence Of Alumina and Silica At 1 273 Kmentioning
confidence: 99%
“…Reduction of iron oxides by solid reductants has also been studied, especially when developing the self reducing iron oxide and carbon composite briquettes. [20][21][22][23][24][25][26][27][28] These studies, with different iron oxides and carbon bearing materials, have shown that the self reduction mechanism and kinetics are more complicated because beside the reaction of reduction it includes sensibly endothermic carbon gasification reaction which very often is found to control the overall rate of self reduction. Moreover, other phenomena could influence 28) (like a devolatilization of the reducing agent) or even control 24) (like a heat transfer) the rate of self reduction.…”
Section: Introductionmentioning
confidence: 99%